Manajemen Sistem Scheduling / Penjadwalan Penggunaan Peralatan Laboratorium Teknik Mesin Universitas Riau Berbasis Komputer - Barib Bramawira; Anita Susilawati; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The scheduling has an important role as a form of decision making. Mechanical Engineering Laboratory of University of Riau is a place to conduct some educational activities such as courses practice, experimental of laboratory, scientific research, teaching practice etc. Therefore, it is necessary to adopt the management information system for scheduling of laboratory equipments. This research aim is to design and develop a system to manage scheduling of data equipments in Mechanical Engineering Laboratory of University of Riau. The laboratory equipments scheduling system in Mechanical Engineering, University of Riau has grooves to come job as dynamic scheduling, which uncertain process the arrival of data equipments, either the number or its arrival. Method in this research used the dynamic scheduling of First Come First Served (FCFS) to determine the priority for decision making. Subsequence, this method was execution of sequence order based on the fastest time of arrival of orders. Developing of an application program used MySQL as database and PHP (Hypertext Preprocessor) as a programming language. Based on the results of testing of the application software were obtained an optimal performance for the management system of scheduling equipments in Mechanical Engineering Laboratory, University of Riau. In conclusion, the new system provided a faster, efficient and accurate of equipments data management in the Mechanical Engineering Laboratory, University of Riau.Keywords: Laboratory Equipment, Dynamic Scheduling, First Come First Served (FCFS), PHP, Database.